2017
DOI: 10.1007/s12042-017-9188-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Introduced Yam Bean (Pachyrhizus spp.) in Three Agro-Ecological Zones of Rwanda

Abstract: The yam bean (Pachyrizhus spp) was recently introduced as a root crop with high-yield potential, considerable protein and micro-nutrient concentration to investigate its potential for food production in Rwanda. Except for Chuin types (Pachyrizhus tuberosus) which have high storage root dry matter (RDM) (26 to 36%), most accessions are consumed raw and are reported to have low RDM. The present study aimed to evaluate and identify adapted high yielding yam bean accessions in major agro-ecological zones of Rwanda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The genetic and phenotypic diversity within P. erosus could be due to geographic isolation and domestication, which is in line with previous studies showing that yam bean genotypes are associated with their respective environment [5,6,10]. P. tuberosus and P. erosus also have genotype-by-environment interactions associated with fresh storage root yield [45] and crop yield [46]. Engelmann's work [9], shows that P. erosus accessions could be divided into four groups based on RAPD analysis: a group of P. erosus that originated from Central America only; two groups that are from Central America and Mexico; and a group that was exclusively made up of accessions from Mexico.…”
Section: Resultssupporting
confidence: 86%
“…The genetic and phenotypic diversity within P. erosus could be due to geographic isolation and domestication, which is in line with previous studies showing that yam bean genotypes are associated with their respective environment [5,6,10]. P. tuberosus and P. erosus also have genotype-by-environment interactions associated with fresh storage root yield [45] and crop yield [46]. Engelmann's work [9], shows that P. erosus accessions could be divided into four groups based on RAPD analysis: a group of P. erosus that originated from Central America only; two groups that are from Central America and Mexico; and a group that was exclusively made up of accessions from Mexico.…”
Section: Resultssupporting
confidence: 86%
“…For instance, Zanklan [ 40 ] observed that reproductive pruning of yam bean led to a great increase in fresh tuber yield including dry matter yield and explained by avoiding the nutrient and water competition between tuber and pod formation, yet a large variation was found among accessions. Similarly, the positive impact of reproductive pruning on fresh storage root yields has been also reported in American yam bean [ 41 , 42 ]. Despite reproductive pruning is a common practice in the yam bean including Mexican and Andean yam bean, more studies are needed in AYB because there are evidences of either adverse or independent effect of pruning and genotype on tuber fresh weight but also interact for tuber dry matter [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies in yam bean reported that root yield ranges from 14 -108 t ha -1 (Nielsen et al, 2000;Belford et al, 2001;Silva et al, 2016;Jean et al, 2017;Vasconcelos et al 2018). In contrast, we found up to 3.53 t ha -1 .…”
Section: Agronomic Traitsmentioning
confidence: 98%
“…When cooked, they serve for preparing cakes and sweets (Silva et al, 2016). Root yield in research ranges from 14 -108 t ha -1 (Nielsen et al, 2000;Belford et al, 2001;Silva et al, 2016;Jean et al, 2017) and at a commercial level 40 -80; 25-65; 24 and 7-17 t ha -1 in Mexico, Thailand, Hawaii, and the Far East, respectively (Phillips-Mora et al, 1993). Its composition ranges from 78 to 94% moisture, 1.0 to 2.2% proteins, 0.0 to 0.8% lipids, 4.6 to 14.9% carbohydrates, 0.5 to 1.4% fibers, and 0.3 to 0.8% ash (Sorensen, 1996).…”
Section: Introductionmentioning
confidence: 99%